International Tax Evasion in the Global Information Age - Kerzner, David S.; Chodikoff, David W.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book provides a comprehensive analysis of the Organisation for Economic Cooperation and Development's (OECD) war on offshore tax evasion. The authors explain the new emerging regulatory regimes on the global exchange of information to combat offshore tax evasion and analyse why Automatic Exchange of Information (AEOI) is not a "magic bullet" solution. Chapters include coverage of the Foreign Account Tax Compliance Act (FATCA), AEOI and the Common Reporting Standards (CRS), and the unprecedented extra-territorial enforcement by the United States of its tax and reporting laws, including the FBAR provisions of the Bank Secrecy Act. These new legal regimes directly impact nearly all financial institutions and financial service providers in the U.S., U.K., EU, Canada, and each of the 132 member jurisdictions of the OECD's Global Forum, as well as 8 million U.S. expats. In light of The Panama Papers, this book offers a timely and valuable contribution on the prevalence and costs of international tax evasion for the global financial community, policy-makers, and practitioners alike.
Chapter 1) Introduction and the Problem of Offshore Tax Evasion -- Chapter 2) International Tax and the Roles of International Tax Policy and Tax Treaties -- Chapter 3) The OECD's War on Offshore Tax Evasion 1996-2014 -- Chapter 4) International Tax Enforcement in Canada -- Chapter 5) International Tax Enforcement in the United States -- Chapter 6) The Role of Canada's Tax Information Exchange Agreements in the Fight against Offshore Tax Evasion -- Chapter 7) Article 26 of the OECD Model Tax Convention on Income and on Capital -- Chapter 8) Automatic Exchange of Information -- Chapter 9) Foreign Account Tax Compliance Act -- Chapter 10) International Collections Enforcement and Voluntary Disclosures -- Chapter 11: Conclusions and Recommendations.
Keywords: Corporations-Finance.; Finance, Public